2018
DOI: 10.1111/odi.12733
|View full text |Cite
|
Sign up to set email alerts
|

Primordial odontogenic tumor: Subepithelial expression of Syndecan‐1 and Ki‐67 suggests origin during early odontogenesis

Abstract: Primordial odontogenic tumor (POT) is composed of variably cellular myxoid connective tissue, surrounded by cuboidal to columnar odontogenic epithelium resembling the inner epithelium of the enamel organ, which often invaginates into the underlying connective tissue. The tumor is delimited at least partially by a thin fibrous capsule. It derives from the early stages of tooth development. Syndecan-1 is a heparan sulfate proteoglycan that has a physiological role in several cellular functions, including mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Previous reports support this hypothesis demonstrating vimentin positivity (POT1‐4 in this study, Bologna‐Molina et al., ) and CD34 positivity (POT1‐5 in this study, Bologna‐Molina et al., ; Ando et al., ). Recently immunoexpression pattern of syndecan‐1 in POTs (POT1‐4 and 6 in this study) were compared with those in tooth germs in late cap and early bell stages, and similar immunopositivity in subepithelial mesenchymal areas were confirmed (Bologna‐Molina et al., ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous reports support this hypothesis demonstrating vimentin positivity (POT1‐4 in this study, Bologna‐Molina et al., ) and CD34 positivity (POT1‐5 in this study, Bologna‐Molina et al., ; Ando et al., ). Recently immunoexpression pattern of syndecan‐1 in POTs (POT1‐4 and 6 in this study) were compared with those in tooth germs in late cap and early bell stages, and similar immunopositivity in subepithelial mesenchymal areas were confirmed (Bologna‐Molina et al., ).…”
Section: Discussionsupporting
confidence: 72%
“…Enamel organ‐like structures are rarely observed within epithelial layers, and it was suggested that the columnar epithelium correspond to the inner enamel epithelium, and cuboidal and squamous epithelium from the middle to outer epithelial layers could correspond to outer enamel epithelium and stratum intermedium (Mikami et al., ). Immunohistochemical analysis demonstrated that the expression of Ki‐67 in the epithelium is lower than 2% while it increase up to 5% in mesenchymal components (average 3.1%) suggesting that POT is a slowly growing tumour (Bologna‐Molina et al., , ). To date, the largest size of the reported tumours was 90 × 70 mm in a 3‐year‐old child (Mosqueda‐Taylor et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent immunohistochemical studies suggest the activity of both epithelial and mesenchymal components during the histogenesis of POT, justifying its inclusion within the group of mixed epithelial and mesenchymal odontogenic tumors in the current WHO classification [9,13]. Epithelial cells are strongly positive for CK14, CK19, and Glut-1, whereas mesenchymal cells are strongly positive for vimentin and syndecan-1 (CD138) [9,10,13,14]. Epithelial cells were Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the tumour recalls the primary stages of tooth development where neither dentin nor enamel are produced. Their presence, in the case reported by Sun et al ., clearly suggests the possibility of a developing odontoma. Odontoblastic differentiation is evident in the epithelial–mesenchymal interface (as seen in the histopathological image); POT is a benign tumour that originates from early odontogenesis and therefore does not induce odontoblastic differentiation and production of dentin proteins with subsequent presence of dental mineralised tissues Absence of cellularity in the subepithelial region: most of the reported POTs show a remarkable cellularity in the interface between the epithelium surrounding the lesion and the underlying mesenchymal tissue, similar to the papillary condensation that occurs in this area during odontogenesis …”
mentioning
confidence: 89%
“…The lesion is covered, at least partly, by a delicate fibrous capsule . Due to the histological characteristics and the lack of production of dental mineralised tissues, this tumour resembles the early stages of odontogenesis, hence the name ‘primordial’; consequently, the differential diagnoses has to include other odontogenic tumours rich in dental papilla‐like fibrous tissue, such as ameloblastic fibroma and odontogenic myxoma …”
mentioning
confidence: 99%